2006
DOI: 10.1300/j074v18n01_05
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Senior Center Friendships on Aging Women Who Live Alone

Abstract: Elderly women who live alone are considered at greater risk for loneliness, depression, and decreased mobility. This paper examines the influences of late-life friendships and senior center activities on the health and well-being of aging women living alone. Based on the findings from 274 women living alone it was found that the senior center is an excellent environment where new supportive friendships can easily be formed. These friendships and other center activities have positive mental and physical outcome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
95
0
4

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(105 citation statements)
references
References 30 publications
6
95
0
4
Order By: Relevance
“…Almost all findings in previous empirical studies strongly support the intended goals of senior centers: promoting health and well-being (Fulbright, 2010;Kirk & Alessi, 2002;Pardasani, 2004;Schneider, Chapman, & Voth, 1985) and fulfilling the needs of socialization (Aday, Kehoe, & Farney, 2006;Eaton & Salari, 2005;Fulbright, 2010;Turner, 2004). Senior centers, an integral component of the service delivery network for older people living in the community, play a significant role on the continuum of elder care as they prevent or delay institutionalization (Aday et al, 2006;Felix et al, 2014;Fitzpatrick, McCabe, Gitelson, & Andereck, 2006;Fulbright, 2010;Pardasani, 2004Pardasani, , 2010Pardasani & Thompson, 2012).…”
Section: Introductionmentioning
confidence: 74%
“…Almost all findings in previous empirical studies strongly support the intended goals of senior centers: promoting health and well-being (Fulbright, 2010;Kirk & Alessi, 2002;Pardasani, 2004;Schneider, Chapman, & Voth, 1985) and fulfilling the needs of socialization (Aday, Kehoe, & Farney, 2006;Eaton & Salari, 2005;Fulbright, 2010;Turner, 2004). Senior centers, an integral component of the service delivery network for older people living in the community, play a significant role on the continuum of elder care as they prevent or delay institutionalization (Aday et al, 2006;Felix et al, 2014;Fitzpatrick, McCabe, Gitelson, & Andereck, 2006;Fulbright, 2010;Pardasani, 2004Pardasani, , 2010Pardasani & Thompson, 2012).…”
Section: Introductionmentioning
confidence: 74%
“…For example, 56% of 856 adults identified that people at senior centers are usually the only people with whom they interact during the day and 90% view this contact to be important (Turner, 2004). Since senior centers often provide a context for creating a supportive peer group (Aday et al, 2006), research is needed to determine ways to facilitate connections. Simone and Haas (2013) demonstrated positive effects of engaging in leisure and remaining socially active in old age and called for interventions that help older adults experience leisure.…”
Section: Leisure Engagementmentioning
confidence: 99%
“…Senior centers reduce older adults' loneliness (Boen, Dalgard, Johansen, & Nord, 2010) and provide a context to develop social networks (Aday, Kehoe, & Farney, 2006). Although leisure is a resource for successful aging, few researchers have tried to understand the leisure of adults who use senior centers (Felix et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…More frequent usersof SC programs tend to be more socially involved [32], more socially active, and non-isolated although many live alone [33,34]. In fact, SCs are particularly important as sources of socialization for older women who live alone [27]. Given the importance of social interaction in promoting physical activity [35], social interaction at SCs is critical.…”
Section: Introductionmentioning
confidence: 99%